(untitled) (Journal of the College of Basic Education, 2024)
neglect Consider avoiding family problems that often negatively affect the upbringing of children. Neglect leads to a threat to the life of the family. This behavior takes many forms, including the loss of dialogue with children, children’s distance from what is right, and the lack of a righteous upbringing, which leads to family disintegration, as Islamic Sharia calls for care Imam al-Sadiq, peace be upon him, said: “He who is kind to his family, may God increase his life.”